2020
DOI: 10.11591/ijere.v9i3.20622
|View full text |Cite
|
Sign up to set email alerts
|

Role of gamification in classroom teaching: Pre-service teachers’ view

Abstract: Planning a creative learning environment is not an easy task. Teachers prefer to teach traditionally in chalk-and-talk approach during language teaching. However, this does not fit learners of the 21st Century as they prefer game-like activities instead of pen-and-paper lessons. Hence, the introduction of gamification in classroom would result in immediate enthusiasm and curiosity, which leads to the learners’ willingness to learn. Gamification prepares learners to be active and take responsibility upon their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…Attitude has been recognized as an important variable in adopting gamification in education as well. Notably, studies have been focusing mainly on the students' point of view (e.g., [20]- [23]), neglecting the role of teachers as designers of instruction until recently. While there is a number of studies examining the attitude of teachers towards game-based learning (e.g., [24]- [26]), research on teacher attitudes towards gamified education without using games is less common, is usually explorative, and focuses on teachers from a singular educational level.…”
Section: Attitude Familiarity Experience and Personality In Relation ...mentioning
confidence: 99%
“…Attitude has been recognized as an important variable in adopting gamification in education as well. Notably, studies have been focusing mainly on the students' point of view (e.g., [20]- [23]), neglecting the role of teachers as designers of instruction until recently. While there is a number of studies examining the attitude of teachers towards game-based learning (e.g., [24]- [26]), research on teacher attitudes towards gamified education without using games is less common, is usually explorative, and focuses on teachers from a singular educational level.…”
Section: Attitude Familiarity Experience and Personality In Relation ...mentioning
confidence: 99%
“…All of the respondents in this study reported that they preferred blended learning by combining classroom teaching with online learning. The blended learning concept includes a framing teaching-learning process that incorporates face-to-face, and teaching supported by ICT [31], [32].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, studies by Mee Mee et al (2020), Yasar et al (2020, Aras and Ciftci (2021) and Villarroel et al (2021) pointed out that gamification is not significantly related to improve motivation, because its use could increase anxiety and jealousy among students, besides teachers are just using some digital tools in a forced way due to the context of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand Sainz deAbajo et al (2019) in its comparative analysis carried out in Spain pointed out that the game is a social process that improves motivation and promotes learning, being the incentives that improve motivation, participation, high acceptance and satisfaction among students. In the case of the study presented, the positive and effective impact on motivation is evidenced because the tools used such as kahoot, quizizz and socrative allow the student to participate in the game oriented to problem solving that involves overcoming obstacles and using corrective feedback from the teacher, thus involving the motivational design ARCS of Keller.On the other hand the inquiry ofMee Mee et al (2020) quantitative study conducted in Malaysia and those of Yaşar et al (2020) found frequent problems such as increased anxiety and setbacks in those who failed to receive rewards, as supported by their quasiexperimental study Aras & Çiftçi (2021) in their quasi-experiemtal study in Turkey who used the Instructional Materials Motivation Scale (IMMS) developed by Keller to measure students' motivation in relation to the materials used in teaching, they found a mean IMMS score of 126.28± 16.88 so they determined that there was no statistically Cornejo-Torres y otros Ciencia Latina Revista Científica Multidisciplinar, Ciudad de México, México. ISN 2707-2207/ISSN 2707-2215 (en línea), enero-febrero, 2023, Volumen 7, Número 1 p 3967…”
mentioning
confidence: 99%